Performance Analysis of Low Density Parity Check Codes in Mobile Environment - Kumar, Sachin (My University, 2008)
Low density parity check (LDPC) codes are one of the hottest topics in coding theory today. Originally invented in the early 1960's, they have experienced an amazing comeback in the last few years. Unlike many other classes of codes LDPC codes are already equipped with very fast (probabilistic) encoding and decoding algorithms. LDPC codes are linear block codes constructed by pseudorandom parity check matrices. These codes are powerful in terms of error performance and, especially, have low decoding complexity. While infinite-length LDPC codes approach the capacity of communication channels, finite-length LDPC codes also perform well, and simultaneously meet the delay requirement of many communication applications such as voice and backbone transmissions. Therefore, finite-length LDPC codes are attractive to employ in low-latency communication systems. This thesis mainly focuses on the bandwidth-efficient communication systems using finite-length LDPC codes. In this thesis, a basic bandwidth-efficient coded modulation system, namely LDPC coded modulation, is investigated for additive white Gaussian noise (AWGN), frequency-flat Rayleigh fading channels and Rician fading channels under different modulation techniques. This investigation shows the analysis of bit error rate (BER) performance for these systems under different modulation techniques on additive white Gaussian noise (AWGN), frequency-flat Rayleigh fading channels and Rician fading channels.
M.E. (ECED)
Keywords: Low Density Parity Check codes; Mobile Comm